OVERVIEW OF NUCLEAR FACTOR-KB (NF-KB) AND NON-STRUCTURAL PROTEIN 1 (NS1) IN PATIENTS WITH DENGUE FEVER IN PREMIER HOSPITAL, SURABAYA - Budiutari, Ni Nyoman; Dachlan, Yoes Prijatna; Nugraha, Jusak (Indonesian Journal of Tropical and Infectious Disease, 2019)
Dengue fever (DF) is an acute viral fever caused by RNA virus that is transmitted by Aedes aegypti and Aedes albopictus mosquitoes. DF is also called viral arthropod-borne disease and is accompanied by headaches, joint and muscle pain. The main target of dengue infection is macrophages or monocytes and dendritic cells (DC). Infected DC is caused the viral replication and the endocytosis into endosomal, easier, thus inducing the activation of NF-Ä¸B transcription factor to produce proinflammatory cytokines such as Tumor Necrosis Factor-α (TNF-α), Interleukin-1 (IL-1), IL-6, IL-12 and chemokine. NF-kB is one of the transcription factors involved in the regulation of the expression of various cytokines, chemokines and anti/pro-apoptotic proteins during infection and act as indicator of disease severity. Infected DC cells are secreted NS1 protein which is the co-factor needed for viral replication and can be detected in the first eight days. The level will be higher in the initial phase of fever. The purpose of this study was to analyze the description of NF-kB and NS1 levels in the serum of patients with dengue fever through observational analytic studies through a cross-sectional approach. This study was done on 40 patients with dengue fever and 10 healthies people as negative controls. NS1 was analyzed in serum of Panbio rapid test and NF-kB level were measured by sandwich ELISA. The results are showed positive and negative NS1 results in dengue fever patients. The average NF-kB serum level in dengue fever patients was found to be higher than the control. NF-Ä¸B level in negative NS1 was higher than the NS1 positive group. It is showed that NS1 is detected both in the acute phase. The detection of NF-Ä¸B is showed the involvement of transcription factors in the development of dengue virus infection and has a protective role for host cells.